THE SIGNIFICANCE OF ‘SAPTAGRAM’, THE PORT CITY OF MEDIEVAL BENGAL, IN THE WRITINGS OF BIPRADAS PIPILAI AND MUKUNDARAM - Sayandip Banerjee, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
In this proposed paper I shall be engaged in an analytical study of the importance of the port city, Saptagram, in Medieval Bengal and how its significance represented in the writings of two contemporary celebrated writers ------ Bipradas Pipilai and Mukundaram. From the writings of these two poets we acquire enormous knowledge about Saptagram, its emergence and the eventual downfall of the port city. Therefore, this paper intends to demonstrate the history of Saptagram and its significance as a trading centre in Medieval Bengal, with the help of the writings of the two poets of that period.